Genetic Susceptibility to Type 2 Diabetes Is Associated with Reduced Prostate Cancer Risk - Pierce, Brandon L. (S. Karger AG, 2010)
OBJECTIVE: To examine the collective effects of type 1 (T1D) and type 2 diabetes (T2D) risk alleles on prostate cancer (PCa) risk. METHODS: Using data on 14 and 18 single nucleotide polymorphisms (SNPs) that effect T1D and T2D risk, respectively, we generated risk scores (a ‘risk allele count’ and a ‘genetic relative risk’) for both T1D and T2D for 1,171 non-Hispanic white, PSA-screened PCa cases and 1,101 matched controls from the Cancer Genetic Markers of Susceptibility study. Logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI) for associations between the diabetes risk scores and PCa risk. RESULTS: Both T2D risk scores, but neither T1D score, showed an inverse association with PCa (p < 0.01). These associations remained significant after excluding HNF1B SNP rs4430796 (a known PCa risk factor) from the analysis. The highest quartile of the T2D allele count (>20 risk alleles) was associated with reduced PCa risk (OR = 0.77; CI: 0.60–0.99) compared to the lowest category (<17 risk alleles). CONCLUSIONS: These results suggest that individuals with increased genetic susceptibility to T2D have decreased risk for PCa. This association is consistent with the observation that individuals with T2D are at decreased risk for PCa; however, data on T2D status was not available for this analysis.